PEMANFAATAN TEKNOLOGI FINANSIAL (FINTECH) UNTUK MENINGKATKAN INKLUSI KEUANGAN PADA UMKM - Slamet abdul azis; Rida Prihatni; Etty Gurendrawati (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
Financial inclusion facilitates transactions for micro and small entrepreneurs, so that their businesses can run more smoothly. This study examines the use of financial technology in Micro, Small, and Medium Enterprises (MSMEs). The approach applied in this article is a qualitative approach with a library study or Library Research. The references used come from studies in national and international reputable scientific articles that are in accordance with the research topic. Based on the literature review in the results and discussion, it can be concluded that financial services based on financial technology contribute positively to financial inclusion in Micro, Small, and Medium Enterprises. The impact on MSMEs, in the early stages, the use of Fintech products and services is a crucial period, where special attention is needed to the learning process, adjustments, and proper risk management so that Fintech can be utilized optimally for business sustainability. Fintech providers need to convey information accurately and carry out effective socialization to maintain user trust since the products and services were first introduced.